Emprego de polímeros de impressão molecular na extração de ácido hipúrico e ácido metil-hipúrico em amostras de urina seguido de análise por eletroforese capilar - Boscari, Carolina Nasser (2016)
Millions of workers are affected by diseases linked to exposure to chemicals in the workplace. In Brazil, the Regulatory Standard 7 sets parameters to control occupational exposure, setting reference values, the maximum biological index, the biological material and the analytical method used in determination of biological indicators. Hippuric acid and methyl hippuric acid are metabolites and biological indicators of the toluene and xylenes, respectively, and their determinations in urine samples can monitor the occupational exposition to these solvents. This work describes the synthesis and characterization of a probe impregnated with molecularly imprinted polymer (MIP) to extract hippuric and methyl hippuric acids directly from untreated urine samples, followed by micellar electrokinetic chromatography. The synthesis of selective MIP used reagents as methanol, metilhipúrico acid (template molecule), 4-vinylpyridine, ethylene glycol dimethacrylate, and 4,4'-azobis-4-cyanovaleric acid. The selectivity of the MIP probe was attested in comparison with the non imprinted polymer (NIP) probe. The extraction step occurred at 7 min and the desorption, performed in 50 mM sodium tetraborate buffer pH 10 with 0.5 mM cetyl trimethyl ammonium bromide (CTAB), also in 7 min. The internal standard used was 3-hydroxybenzoic acid (HBA) 1 g L-¹. The system variables were optimized to provide ideal conditions for the extraction and desorption of the analytes, as well as for MEKC analyses. The method was linear from 0.5 to 5.0 g L-¹ for both the analytes, with correlation coefficients > 0.994. The precisions and accuracies, expressed as relative standard deviation and relative error, were < 20.0 and within -15.4 to 16.6%, respectively, in accordance with the FDA recommendation. MIP probe has proven to be simple, cheap, resistant, and synthetically reproducible, being successfully used to analyze hippuric and methyl hippuric acids from real samples.